Diagnostic Efficacy of Xpert MTB/RIF Assay in Bronchoalveolar Lavage Fluid for Tracheobronchial Tuberculosis: A Retrospective Analysis - Sun, Yue; Zhang, Qing; Zhang, Qin; Liu, Chang; Zhang, Hong; Fu, Yinghui; Liu, Yongyu; Hou, Gang (Frontiers in Medicine, 2021)
Background: The Xpert Mycobacterium tuberculosis/rifampin (MTB/RIF) assay has shown good diagnostic efficacy in brushing and biopsy tissue samples from patients with tracheobronchial tuberculosis (TBTB). However, its diagnostic value in bronchoalveolar lavage fluid (BALF) is still unclear. Therefore, the present retrospective study aimed to evaluate the diagnostic value of the Xpert MTB/RIF assay in BALF. Methods: The clinical data of 266 patients with suspected TBTB from January 2018 to October 2020 were pooled with complete details of bronchial brush and bronchoalveolar lavage samples. Smears of the bronchial brushings were stained with Auramine O stain to detect acid-fast bacilli (AFB), and BALF samples were used for culturing MTB with the BACTEC MGIT 960 system and the Xpert MTB/RIF assay. The diagnostic performance of these methods was assessed and compared. Results: A total of 266 patients suspected to have TBTB were enrolled in the final analysis. Of these patients, 179 patients were confirmed to have TBTB and 87 patients were non-TBTB. The sensitivity of the Xpert MTB/RIF assay in BALF (87.2%) was significantly higher than that of the brush smear for AFB (35.2%, p < 0.001). No significant difference was observed between the sensitivities of the Xpert MTB/RIF assay in BALF and MTB culture in BALF (87.2% vs. 84.9%, p = 0.542). The specificities of the Xpert MTB/RIF assay in BALF, MTB culture in BALF, and the bronchial brush smear were 97.7%, 97.7%, and 98.9%, respectively. The positive predictive value (PPV) and negative predictive value (NPV) of the Xpert MTB/RIF assay in BALF, MTB culture in BALF, and the bronchial brush smear were 98.7% and 78.7%, 98.7% and 75.9%, and 98.4% and 42.6%, respectively. Among the MTB culture-positive patients with TBTB detected by the Xpert assay, 27.0% (20/74) were identified to be resistant to RIF. Conclusions: The Xpert MTB/RIF assay in BALF enables a rapid and accurate diagnosis of TBTB and identification of RIF resistance, which is crucial for timely and proper treatment. Moreover, in patients with TBTB, BALF could be used as an alternative to bronchial brushing and biopsy tissues for the Xpert MTB/RIF assay.